Planning of the offer of SBB - Grossenbacher, Peter (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
In his article, the author describes the planning process at the Swiss Federal Railways for new train service offers for passenger traffic, as seen from the standpoint of the Division Passenger Traffic. The emphasis is laid on the planning of future timetables, in cooperation with the concerned organisation units of the other divisions, Freight and Infrastructure. The discrimination-free planning process for the different time stages is also presented using various modern planning instruments such as Viriato and Polydrom. Thereby it is clearly stated that in timetable planning, also much creativity and many innovative ideas are needed in order to satisfy market requirements. In addition, the timetables form an element of a comprehensive offer and must be harmonized with the other marketing instruments to reach an optimal marketing mix.